The World Bank and public sector management: What next - Pritchett, Lant (2013)
The new World Bank strategy on Public Sector Management (PSM) has to be judged against the magnitude of the problems it faces. Two of these are what to do about failed and failing states and what to do about the stagnation of progress in 'flailing' states. On both of these fronts the gap between what the world of action wants - an implementable action plan to tackle tough problems like Afghanistan - and what the PSM strategy does (and quite probably can) deliver is wide. This article proposes 'problem-driven iterative analysis' as one way of bridging the gap. - Reproduced.
Keywords: World Bank; Public administration